2020
DOI: 10.3390/su12103973
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Its Implications for Rural Economies

Abstract: This paper presents a rapid assessment of current and likely future impacts of the COVID-19 outbreak on rural economies given their socio-economic characteristics. Drawing principally on current evidence for the UK, as well as lessons from the 2001 Foot and Mouth Disease outbreak and the 2007/8 financial crises, it outlines the likely key demand and supply effects, paying attention to the situation for agriculture as well as discussing the implications for rural communities. A distinction is made between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 21 publications
4
116
0
7
Order By: Relevance
“…The above discussion is part of a wider picture as there are rural areas facing a new challenging environment [24] and there are contradicting views regarding the rural development model that it has to frame the development programmes [25] since rural areas are multi-impacted and multi-influenced [26] by the policy approaches and mix followed [27]. To this extent, we argue that the research interest in EU development programmes implemented in the past or present for rural tourism enterprises in Greece is still at the starting point and a multilayered illustration of the obstacles in the EU funds absorption capacity of rural tourism enterprises can contribute to academic debate.…”
Section: Introductionmentioning
confidence: 99%
“…The above discussion is part of a wider picture as there are rural areas facing a new challenging environment [24] and there are contradicting views regarding the rural development model that it has to frame the development programmes [25] since rural areas are multi-impacted and multi-influenced [26] by the policy approaches and mix followed [27]. To this extent, we argue that the research interest in EU development programmes implemented in the past or present for rural tourism enterprises in Greece is still at the starting point and a multilayered illustration of the obstacles in the EU funds absorption capacity of rural tourism enterprises can contribute to academic debate.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them analyzed solely the impact of the virus on agricultural production regarding the first infected by COVID-19 countries, namely China [18,19] and later Italy [7,[20][21][22]. In contrast, some studies dealt with the agricultural sector of countries, which were later infected by the viral pandemic, including countries from the rest of Asia (India [23,24] and Iran [25]), Oceania (Australia [26] and New Zealand [27]), Europe (rest of EU [5,28] and the United Kingdom (UK) [29]) as well as America (Argentine [30], Peru [31], Canada [32][33][34][35][36] and the US [14,37,38]).…”
Section: Pandemic Effects On Agriculutral Sectormentioning
confidence: 99%
“…In the beginning, at least for the countries in the northern hemisphere, this was not a huge problem. However, the harvest of vegetables and fruits that are mostly perishable had declined due to labour shortages (Stephens et al, 2020;Phillipson et al, 2020). Research conducted for southern Italy showed the importance of temporary labour for farm-level operations.…”
Section: Effects Of Covid-19 On Agriculture and The Food Systemmentioning
confidence: 99%